Broken Rotor Bar Diagnosis via Monitoring Current Spectrum Analysis in Micro Wind Turbine Induction Motor - Mahmood, Faleh H.; Kadhim, Hussein T.; Resen, Ali K. (Iraqi Journal of Science, 2021)
Micro wind turbines are generally used in remote locations, and it is difficult and expensive to repair faults which forced the need for condition monitoring and fault diagnosis which has not been used extensively for small turbines. The possibility of utilizing Fast Fourier Transform (FFT) for diagnosis the faults of broken rotor bar in squirrel cage induction motor of a micro wind turbine was investigated. Monitoring and analysis the current spectrum can be effective for diagnosis the early stage of faults and avoid complete catastrophic failure in the motor by powerful virtual instruments and LabVIEW software as an integral part of this instrumentation. Combination advanced signal processing technique with computerized signal processing and high accuracy data acquisition offer a new approach for monitoring spectral analysis of rotor bar fault in an induction motor. The theoretical rule of this method was proved by laboratory experiment.